Tiller Number1 encodes an ankyrin repeat protein that controls tillering in bread wheat - Chunhao Dong; Lichao Zhang; Qiang Zhang; Yuxin Yang; Danping Li; Zhencheng Xie; Guoqing Cui; Yaoyu Chen; Lifen Wu; Zhan Li; Guoxiang Liu; Xueying Zhang; et al. (Nature Communications, 2023)
Abstract Wheat (Triticum aestivum L.) is a major staple food for more than one-third of the world’s population. Tiller number is an important agronomic trait in wheat, but only few related genes have been cloned. Here, we isolate a wheat mutant, tiller number1 (tn1), with much fewer tillers. We clone the TN1 gene via map-based cloning: TN1 encodes an ankyrin repeat protein with a transmembrane domain (ANK-TM). We show that a single amino acid substitution in the third conserved ankyrin repeat domain causes the decreased tiller number of tn1 mutant plants. Resequencing and haplotype analysis indicate that TN1 is conserved in wheat landraces and modern cultivars. Further, we reveal that the expression level of the abscisic acid (ABA) biosynthetic gene TaNCED3 and ABA content are significantly increased in the shoot base and tiller bud of the tn1 mutants; TN1 but not tn1 could inhibit the binding of TaPYL to TaPP2C via direct interaction with TaPYL. Taken together, we clone a key wheat tiller number regulatory gene TN1, which promotes tiller bud outgrowth probably through inhibiting ABA biosynthesis and signaling.